Ac2-26 mimetic peptide of annexin A1 inhibits local and systemic inflammatory processes induced by bothrops moojeni venom and the lys-49 phospholipase A2 in a rat model - Stuqui, Bruna [UNESP]; Paula-Silva, Marina de [UNESP]; Carlos, Carla Patrícia [UNESP]; Ullah, Anwar [UNESP]; Arni, Raghuvir Krishnaswamy [UNESP]; Gil, Cristiane Damas; Oliani, Sonia Maria [UNESP] (Public Library Science, 2015)
Annexin A1 (AnxA1) is an endogenous glucocorticoid regulated protein that modulates anti-inflammatory process and its therapeutic potential has recently been recognized in a range of systemic inflammatory disorders. The effect of the N-terminal peptide Ac2-26 of AnxA1 on the toxic activities of Bothrops moojeni crude venom (CV) and its myotoxin II (MjTX-II) were evaluated using a peritonitis rat model. Peritonitis was induced by the intraperitoneal injection of either CV or MjTX-II, a Lys-49 phospholipase A2. Fifteen minutes after the injection, the rats were treated with either Ac2-26 or PBS. Four hours later, the CV and MjTX-II-induced peritonitis were characterized by neutrophilia (in the peritoneal exudate, blood and mesentery) and increased number of mesenteric degranulated mast cells and macrophages. At 24 hours post-injection, the local inflammatory response was attenuated in the CV-induced peritonitis while the MjTX-II group exhibited neutrophilia (peritoneal exudates and blood). Ac2-26 treatment prevented the influx of neutrophils in MjTX-II-induced peritonitis and diminished the proportion of mesenteric degranulated mast cells and macrophages in CV-induced peritonitis. Additionally, CV and MjTX-II promoted increased levels of IL-1β and IL-6 in the peritoneal exudates which were significantly reduced after Ac2-26 treatment. At 4 and 24 hours, the endogenous expression of AnxA1 was upregulated in the mesenteric neutrophils (CV and MjTX-II groups) and mast cells (CV group). In the kidneys, CV and MjTX-II administrations were associated with an increased number of macrophages and morphological alterations in the juxtamedullary nephrons in proximal and distal tubules. Ac2-26 promoted significant recovery of the juxtamedullary structures, decreased the number of macrophages and diminished the AnxA1 in epithelial cells from distal tubules and renal capsules. Our results show that Ac2-26 treatment significantly attenuates local and systemic inflammatory processes and indicate this peptide as a potential target for the development of new therapeutic strategies for the snakebite envenomation treatment.